Psychopsychic Practice of Shalawat Al-Husainiyah at Jama'ah Al-Khidmah - Basri, Ahmad Faizal (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2025)
This study aims to explore the practice of jama'ah al-Khidmah towards shalawat al-Husainiyyah. There is ana interesting phenomenon, starting pocketing, reading and understanding the content of shalawat al-Husainiyyah. The shalawat contains 30 different themes along with verses from Alqur’an, whether the verses are whole or truncated and such verses are legal because as an interpretation of verses with verses of the mawdu'i al-Wajiz type or reading the Qur'an as practiced by Bilal ra. But still follow the rool of waqaf- ibtida'. The discussion is the basis of the text for placing these verses, the impact of practice and the practices of jama'ah al-Khidmah as representative of the values in shalawat al-Husainiyyah. The method used is the living Qur'an with a psychospiritual approach. The results of this study: impact of practice on the basis of exchatological and practical performative suggestions is facilitating sustenance, calming the heart, finding solutions, beautifying morals and behavior, the requested and expected wishes can be fulfilled, protected from shame and shortcomings, and elevated in rank, and recognized as a student of Syaikh Achmad Asrori al-Ishaqi. There are also those who practice and understand the content of shalawat al-Husainiyyah which has a bigger and better impact, because the Qur'an is a guide to life based on the stages of cognition, internalization and affirmation through the interpretation of shalawat al-Husainiyyah and an informative representative of shalawat al-Husainiyyah on the practices of the al-Khidmah congregation, including lots of dhikr and praying after fardhu prayers according to al-Ishaqi's demands, increasing blessings on the Prophet Muhammad, especially in the month of Ramadan, following the Dzikr Assembly organized by the Jama'ah al-Khidmah Management so that we can dzikr and pray together.